The Effectiveness of Learning Media in Waste Management - Br Tarigan, Lidia; Rogaleli, Yuanita C.L.; Dukabain, Olga Mariana (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
The involvement of the community affects the effectiveness of waste management. By offering suitable media under local conditions, community participation can be increased. This research aims to determine how well educational materials can raise awareness of waste management issues and encourage community involvement. The research method used quasi-experimental. The efficacy of learning media, research variables, respondent knowledge, and waste management follow-up. Representatives from 46 different community groups made up the study subjects. Surveys, pre-and post-tests, and questionnaires were employed to collect data. A paired t-test was utilized to evaluate the data after it had been processed descriptively. The knowledge of the respondents increased by 24%. The results show a significant difference in knowledge between before and after using learning media, according to the results of the paired t-test (p = 0.000). The learning media effectiveness test results showed no difference between book media and leaflet media in increasing respondents' knowledge (p=0.130). Follow-up plans, forming a waste bank (33.3), and sharing the information obtained with other parties (73.8%). The conclusion is there is a significant difference in knowledge before and after using learning media (p = 0.000). There was no difference between book media and leaflet media in increasing respondents' knowledge (p=0.130). The public can utilize books and leaflets to increase their knowledge about waste management.